Investigating Test-Taking Strategies in an English Reading Comprehension Test Used by Secondary High School Students - Hasanah, Nur Faridatul; Iswari, Weningtyas Parama; Hermagustiana, Istanti (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2024)
Reading is a crucial skill that Indonesian learners are expected to master, as outlined in the 2013 Curriculum. Students are required to develop comprehension skills to understand both explicit and implicit information in a text. To assess students’ knowledge, teachers often use tests. During these reading tests, students may employ strategies to aid their comprehension. This study investigates the strategies used by secondary high school students at MA Darul Ihsan Samarinda during an English reading comprehension test, along with the challenges they face when using these strategies. This study employs a qualitative design to examine the strategies utilized by six students: high score, middle score, and lowest score. The data, gathered through the think-aloud method and interviews, is analyzed using thematic analysis. The findings reveal that students employed 23 out of 31 strategies to answer factual questions and 19 strategies for inferential questions. Both the high score and middle score students predominantly used the strategy of reading the text for clues in both types of questions. Conversely, the lowest score student primarily relied on the strategy of rereading the question. Despite the differences, all students utilized a meaning-based text strategy to choose their answers. The middle score and lowest score students frequently faced challenges with time management and complex vocabulary. Additionally, using mixed-method research designs could provide deeper insights into test-taking strategies. This study focused on the strategies used by high school students during reading tests, while other research has examined test-taking strategies in high-stakes language tests